Trabalho e educação: os coletivos pedagógicos de Makarenko - Tillmann, Reinaldo Luiz Xavier (2009)
The present thesis focuses on the subservience bias that the capitalist work relations go through, supported by the teachings of Émile Durkheim upon analyzing the process of social division of work. Confronting Durkheim s complexity, it considers Marx s revelations on the possibility of emancipation grounded on an educational principle which exists in the labor environment that is structured on the understanding of what Karl Marx defines as the emancipation of all mankind towards a new awareness of the social division of work. It points to the pedagogical collectivities which were reported and experienced by Anton MakarenKo as a possible description of Marx s emancipation process and speculates that the university may be the propelling agent for the emergency of an educational principle present in our contemporary world.